2021
DOI: 10.1002/adfm.202101593
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Ion Desolvation Induced by Nitrate Additives Reveals New Insights into High Performance Lithium Batteries

Abstract: Electrolyte additives have been widely used to address critical issues in current metal (ion) battery technologies. While their functions as solid electrolyte interface forming agents are reasonably well‐understood, their interactions in the liquid electrolyte environment remain rather elusive. This lack of knowledge represents a significant bottleneck that hinders the development of improved electrolyte systems. Here, the key role of additives in promoting cation (e.g., Li+) desolvation is unraveled. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 60 publications
2
81
0
Order By: Relevance
“…[9][10][11][12][13][14][17][18][19][20][21][22] Importantly, the class of ternary bismuth-based materials, such as in Bi-S-I in this work and previously reported BiSbS 3 , 11 suggest an outstanding performance as battery electrodes over the binary bismuth-based materials as well as the state-of-theart graphite anode (theoretical capacity of 372 mAh g -1 ). 23,24 Furthermore, these materials merit further investigations of which include applications in other type of batteries such as multivalent metal ions (e.g., Zn 2+ , Mg 2+ , and Al 3+ ) battery systems. In summary, we report a controlled synthesis of Bi 13 S 18 I 2 and BiSI by simply tuning the sulfur concentration in a nonaqueous medium and demonstrate their potential as anode materials for rechargeable batteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][17][18][19][20][21][22] Importantly, the class of ternary bismuth-based materials, such as in Bi-S-I in this work and previously reported BiSbS 3 , 11 suggest an outstanding performance as battery electrodes over the binary bismuth-based materials as well as the state-of-theart graphite anode (theoretical capacity of 372 mAh g -1 ). 23,24 Furthermore, these materials merit further investigations of which include applications in other type of batteries such as multivalent metal ions (e.g., Zn 2+ , Mg 2+ , and Al 3+ ) battery systems. In summary, we report a controlled synthesis of Bi 13 S 18 I 2 and BiSI by simply tuning the sulfur concentration in a nonaqueous medium and demonstrate their potential as anode materials for rechargeable batteries.…”
mentioning
confidence: 99%
“…9–14,17–22 Importantly, the class of ternary bismuth-based materials, such as Bi–S–I in this study and previously reported BiSbS 3 , 11 suggest outstanding performance as battery electrodes over the binary bismuth-based materials and the state-of-the-art graphite anode (theoretical capacity of 372 mA h g −1 ). 23,24 Furthermore, these materials merit further investigations, which include applications in other types of batteries, such as multivalent metal ion ( e.g. , Zn 2+ , Mg 2+ , and Al 3+ ) battery systems.…”
mentioning
confidence: 99%
“…Numerous methods have been proposed to address these problems including electrolyte additives, [34][35][36][37][38][39][40][41][42][43][44][45] artificial SEI, [46][47][48][49][50][51][52][53][54][55][56] superconcentrated electrolyte, [57][58][59][60][61][62][63][64][65][66][67][68][69][70] solid-state electrolyte (SSE), [71][72][73][74][75][76][77][78][79][80] functional membrane, [81][82][83][84]…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyte additives such as fluorinated ethylene carbonate (FEC) (Zhang X.-Q. et al, 2017;Hou et al, 2019;Lin and Zhao, 2020), LiNO 3 (Zhang et al, 2021a;May et al, 2021;Piao et al, 2021;Wahyudi et al, 2021) and vinylene carbonate (VC) (Kuwata et al, 2016; are beneficial for forming stable SEI layers and inhibiting the growth of the lithium dendrites. The application of the gel electrolytes with high conductivity or solid electrolytes with high mechanical strength to replace the conventional liquid electrolytes also reached great achievements in improving the cycling stability.…”
Section: Introductionmentioning
confidence: 99%